PENENTUAN HARGA JUAL PADA RUMAH MAKAN PAK JENGGOT GADING CEMPAKA KOTA BENGKULU - Endah Heryanti; Derri Mulya Vebrianto; Lovia Mulyana Sari (JURNAL LENTERA AKUNTANSI, 2021)
The research entitled Determination of Selling Prices at Pak Jenggot's Restaurant, setting prices for each company is different not only in how they determine it but also with what process to determine the price of an item and the selling price of a product needs to be set to achieve profit. The selling price of a production affects the position of market competition and will further affect production volume. It can be said that the selling price affects the size of the company's revenue and net profit. The accuracy of determining the selling price is included in the right strategy to determine the extent to which consumers are satisfied with a product. The reason for this research is to find out more about determining the selling price of Pak Beard's restaurant according to accounting. This writing also aims to find out what menus are available, the elements of production costs and determining the selling price using the methodcost-plus pricing and the cost of production with the method full costing at Mr. Beard's Restaurant. The data collected in this study is data on production costs which include raw material costs, indirect raw materials, direct labor costs,overhead factory, and operating costs which include marketing costs and administrative costs. Data collection methods with interviews and documentation. Key words: Selling price, Cost-Plus Pricing, Cost Of Goods Sold Full Costing